Influence of Al content on thermal stability of nanocrystalline AlxCoCrFeNi high entropy alloys at low and intermediate temperatures - Garlapati, Mohan Muralikrishna; Vaidya, Mayur; Karati, Anirudha; Mishra, Soumyaranjan; Bhattacharya, Rahul; Murty, B. S. (Advanced Powder Technology, 2020)
Thermal stability of mechanically alloyed nanocrystalline AlxCoCrFeNi (x = 0, 0.3, 0.6, 1 mol) high entropy alloys (HEAs) has been investigated for the low and intermediate temperature range of 673–1073 K. Single phase FCC structure is observed in the as milled CoCrFeNi. A mixture of FCC and BCC phases is exhibited by × = 0.3, 0.6 and 1, alloys where the volume fraction of BCC increases with increasing Al content. Phase evolution in heat-treated AlxCoCrFeNi HEAs proceeds via increasing BCC fraction at 673 K, followed by subsequent reduction at elevated temperatures. For each alloy, the major phase observed in as milled condition and it is retained even after prolonged exposure at the 1073 K. Al favors the formation of the BCC phase due to its high affinity to form ordered B2 structures with constituent elements Co, Fe and Ni. Thermal exposure of AlxCoCrFeNi HEAs also leads to the formation of Cr7C3, owing to the higher negative free energy of carbide formation for Cr among other constituents. Transmission electron microscopy (TEM) investigations substantiated that nanostructure of milled powder is maintained even after the heat treatment. Grain growth factor for quinary HEAs is relatively lower than quaternary CoCrFeNi owing to their slower rates of diffusion.
Publisher Copyright: © 2020
Keywords: AlCoCrFeNi; High entropy alloys; Mechanical alloying; Nanocrystalline; Thermal stability